“DEFENDS” as An Effective Writing Strategy to Create Students Creativity - Mu'alim Ibnu Fathoni; Sumardi Sumardi; Slamet Supriyadi (Universitas Jambi, Magister Program of English Education Department, 2019)
In the educational process, specifically in the classroom, students must be able to produce good writing in academic writing that is relevant to the topic that is given or determined by the teacher. Most students get difficulty in learning writing moreover producing good writing. Teachers need to help the students build their habits of writing creatively. DEFENDS, a strategy that was developed by Ellis (1989,1990,1993) can help students to defend a particular position in a written assignment, improve writing strategies, facilitate writing process, and strengthen learning to learn writing skill. DEFENDS strategy gives students the means to plan before they begin writing. This strategy guides students to be an independent writer through several stages (Decide, Estimate, Figure, Express, Note, Drive, and Search). Students are demanded to have not only language skill but also other factors such as creativity. Creativity gives a contribution in education field nowadays, the issue of creativity has brought to the forefront of educational policy and practice, including the importance of creativity in writing. Research dealing with creativity in writing is needed. This research was an experimental design called post-test design using 2x2 factorial arrangements. The sample was high school students. Two instruments used by the researcher; those were writing test and creativity test. The value of Ftable at the level of significance is α = 0.05 is 4.01, while the value of Fo between columns is 5.734141. Fo between rows (16.5821) is higher than Ft at the level of significance α = 0.05 (4.01), and Fo columns by rows (9.21) are higher than Ft at the level of significance α = 0.05 (4.01).